Political theorists in context - Sparks, Chris, 1956-; Isaacs, Stuart (London ; New York, N.Y. : Routledge, 2006)
Focusing on the historical context in which political theorists have developed their thinking, this textbook provides an invaluable introduction to students of political thought. The authors address a series of canonical major thinkers in the context of three world-changing epochs: the English, French and Industrial revolutions. The theorists' ideas are assessed with reference to the politics of their time and show how they responded to, or interacted with, the political events and issues of their day.
Includes bibliographical references and index.
Keywords: Political science -- History; Political development -- History; Ideology -- History; Social conflict; Elite (Social sciences)